Management of Ingested Foreign Bodies in Childhood. Issue 5785 (20th November 1971) - Spitz, Lewis
Abstract : A total of 660 patients with ingested foreign bodies admitted to the general surgical services in two children's hospitals in Liverpool are reviewed. Endoscopic removal (205 cases) is recommended for all foreign objects impacted in the oesophagus, with the exception of rounded or blunt objects in the lower third, which should be observed for a maximum of 12 hours. The indications for laparotomy for removal of a foreign body (43 cases, 6·5%) are the danger of perforation and failure of progression. The ingestion of a long slender object—for example a hair-grip—in a child under 2 years of age, is an absolute indication for prophylactic operative removal owing to the high incidence of impaction and perforation of the duodenum.